2021
DOI: 10.1038/s41380-021-01315-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural gray matter differences in Problematic Usage of the Internet: a systematic review and meta-analysis

Abstract: Problematic Usage of the Internet (PUI) has been linked to diverse structural gray matter changes in individual data studies. However, no quantitative synthesis across studies has been conducted. We aimed to identify gray matter regions showing significant spatial convergence across neuroimaging studies in PUI. We searched PubMed and PsycINFO up to 10/03/2021 and included original, cross-sectional comparative studies that examined structural gray matter imaging in PUI versus control groups; reported a whole-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 77 publications
2
16
0
1
Order By: Relevance
“…Those addicted to gaming have poorer response inhibition, working memory, decision-making, and emotion regulation, which is associated with reduced prefrontal cortex functioning (Kuss, Pontes, & Griffiths, 2018 ). Recent meta-analysis studies have found that people with problematic internet usage (PIU) have cognitive impairments including motor inhibitory control, working memory, and decision-making and decreased gray matter in the dorsolateral prefrontal cortex and anterior cingulate cortex, which are implicated in reward processing, decision making and top-down inhibitory control (Ioannidis et al, 2019 ; Solly, Hook, Grant, Cortese, & Chamberlain, 2021 ). Increased EEG FC in the alpha and beta frequency bands within the right hemisphere may be involved in the recurrent activation of visuospatial working memory and executive function due to excessive gaming (Burleigh, Griffiths, Sumich, Wang, & Kuss, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those addicted to gaming have poorer response inhibition, working memory, decision-making, and emotion regulation, which is associated with reduced prefrontal cortex functioning (Kuss, Pontes, & Griffiths, 2018 ). Recent meta-analysis studies have found that people with problematic internet usage (PIU) have cognitive impairments including motor inhibitory control, working memory, and decision-making and decreased gray matter in the dorsolateral prefrontal cortex and anterior cingulate cortex, which are implicated in reward processing, decision making and top-down inhibitory control (Ioannidis et al, 2019 ; Solly, Hook, Grant, Cortese, & Chamberlain, 2021 ). Increased EEG FC in the alpha and beta frequency bands within the right hemisphere may be involved in the recurrent activation of visuospatial working memory and executive function due to excessive gaming (Burleigh, Griffiths, Sumich, Wang, & Kuss, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PubMed and PsycINFO were searched up to 2 nd May 2022 using the following string, adapted from previous meta-analyses related to PUI [ 13 , 14 ]: (“drug” OR “medication*” OR “pharmacol*”) AND (“internet use” OR “internet addiction” OR “smartphone use” OR “smartphone addiction” OR “gaming addiction” OR “internet gaming disorder” OR “PIU” OR “PUI”). Terms related to “smartphone” addiction were used to ensure that the search included studies relevant to Internet use regardless of modality, while those related to “gaming” addiction were used to ensure IGD studies were included, as much of the available PUI literature focuses on this field.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies mainly addressed issues surrounding internet addiction [ 8 ] without focusing on the use of smartphones, which have become an indispensable communicating device in over 83% of the global population [ 8 ]. Although a previous meta-analysis has reported a reduction in gray matter volume (GMV) as well as significant activations in the medial/superior frontal gyri, the left anterior cingulate cortex/cingulate gyrus, and the left middle frontal/precentral gyri in individuals with internet addiction [ 9 ], the structural and functional impacts of excessive smartphone use on the central nervous system remains unclear. Therefore, the current meta-analysis aimed at investigating the difference in structural volume and functional connectivity between individuals with excessive smartphone use and their comparators with regular use.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the most popular assessment tool for macroscopic neuroanatomical assessment of the brain (e.g., brain volume measurement) because of its excellent image resolution and quality of between-tissue contrast [ 10 ]. Consistently, MRI has been used to examine anatomic differences (e.g., gray matter volume) among individuals with behavioral addiction [ 9 , 11 ]. MRI systems of different magnetic strengths have their distinct merits in MRI acquisition.…”
Section: Introductionmentioning
confidence: 99%